Application of design for Six Sigma methodology to an automotive component. (2016) - Suresh, Kumbhar Mahesh; Asokan, P.; Vinodh, S.
Six Sigma strategy applies Define, Measure, Analyse, Improve and Control method, which is best suited for effective process improvements. In order to build quality within products during design stage, a pre-emptive approach Design for Six Sigma (DFSS) is required. Most quality techniques are based on production and shop floor associated tasks. Most drawbacks or errors in product occur during design phase itself. The improvement of process after it is rolled into production has inbuilt constraints. Hence, it is found vital that improving a product during design phase is much feasible than bringing improvements during further phases. This study explores the scope of the DFSS approach to product development, during early stage of the product design process. It includes execution of Identify, Design, Optimise, Validate (IDOV) phases with proper tools. DFSS for design improvement is applied to an automotive component using IDOV phases. O-Ring in automotive assembly was selected as case project.